2018
DOI: 10.1007/s00345-018-2390-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing urinary retention after transperineal template biopsy of the prostate: outcomes from a regional cancer centre

Abstract: Factors resulting in an increased risk of urinary retention are advancing age (> 68.7 years); a larger prostate volume (> 75 cc); greater number of biopsies (> 35); greater severity of lower urinary tract symptoms prior to biopsy and diabetes. Targeted biopsies alone, instead of a full template, may avoid urinary retention in the high-risk groups identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 16 publications
1
26
0
1
Order By: Relevance
“…It is possible that the higher incidence of instrumentation-related trauma induced by the increased number of cores during the biopsy procedure could account for the disparity in the incidence rates. To further support this assertion, Kum et al [8] reported a postbiopsy AUR incidence rate of 12.8% in their 32-35 core biopsy, which is over three times the rate observed in this study. The marked disparity in these values could be due to the lower mean age (64.9 years) in our study compared to the result (66.2 years) of their study.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…It is possible that the higher incidence of instrumentation-related trauma induced by the increased number of cores during the biopsy procedure could account for the disparity in the incidence rates. To further support this assertion, Kum et al [8] reported a postbiopsy AUR incidence rate of 12.8% in their 32-35 core biopsy, which is over three times the rate observed in this study. The marked disparity in these values could be due to the lower mean age (64.9 years) in our study compared to the result (66.2 years) of their study.…”
Section: Discussionsupporting
confidence: 78%
“…The findings of this study thus re-enforce the assertion of Bozlu et al [9] that worsening of IPSS is transient in the patients. The result of this research also revealed that the patient sub-group with moderate IPSS values (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)) at baseline had a significant increase in mean total IPSS scores 7 days after the biopsy, while those with mild or severe symptoms did not experience a significant change in their symptom score. Voiding dysfunction is defined by an IPSS voiding to storage symptoms ratio of greater than 1.0 [12].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…According to Kum et al, 16 31 of the 243 patients (12.8%) developed urinary retention. In a study by Buskirk et al, 13 11.5% of the patients developed AUR within 48 hours of the biopsy.…”
Section: Discussionmentioning
confidence: 98%
“…[10][11][12][13][14][15] Additionally, studies have assessed the factors predictive of AUR after TTMB. 6,13,16 The factors identified include advanced age, large prostate volume, greater number of biopsies performed, higher severity of lower urinary tract symptoms before biopsy, and diabetes. 13,16 However, previous studies were conducted on Western populations, and there has been no study involving Korean patients.…”
Section: Introductionmentioning
confidence: 99%